Barriers of Adopting Online Learning Among the University Students in Bangladesh During Covid-19 - Md. Tariqul Islam; Tasnim Ibnat Habib (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2022)
Due to the COVID-19, all the educational institutions in Bangladesh were forced to stop the traditional face-to-face learning method and adopt the online learning system to resume the students’ learning activities, even though no one was prepared for that. The current study aims to identify the barriers to adopting online learning during this pandemic from the perception of university students of Bangladesh. The present study is a quantitative study and that has been conducted by performing a survey on 394 university students of Bangladesh with the help of a semi-structured online questionnaire. The current study is a cross-sectional study in nature, and the convenience sampling technique was adopted to carry out this study. The study found that the adoption of online learning of university students in Bangladesh is disrupted by several environmental and situational barriers, e-learning barriers, and psychological barriers. The current study provides insights into the barriers to adopting online learning among university students of Bangladesh. This study has both theoretical and practical contributions; theoretically, the current study provides a research framework to identify the barriers of adopting online learning, and practically, the findings of the study provide a brief concept of the barriers of online education to the stakeholder of the education industry of Bangladesh which will be beneficial for them to take proper initiatives to minimize these barriers. Finally, the current study was concluded by indicating some limitations and providing the directions for future research.